Shear-induced Notch-Cx37-p27 axis arrests endothelial cell cycle to enable arterial specification - Jennifer S. Fang (Nature Portfolio, 2017)
New vessel formation relies on a tightly controlled switch in endothelial biology from proliferating to  specializing phenotypes. Here, Fang et al. elucidate the molecular mechanisms of this switch and show that the arterial shear activates a Notch-Cx37-p27 axis promoting endothelial cell cycle arrest and enabling arterial gene expression.